Representação política e participação social: uma abordagem a partir da experiência dos conselhos de políticas públicas e das conferências nacionais - Chagas, Francisco Yrallyps Mota (2016)
The purpose of this paper is to revisit the idea of political representation that was forged in modernity to adapt it to the current context of contemporary democracies, which increasingly seek to promote social participation in decisions that are taken in the political public sphere. It adopts as a parameter the regime inaugurated by the Constitution of the Federative Republic of Brazil of 1988. In analyzing this new regime, it is argued that the 1987-1988 Constituent sought to privilege and stimulate social participation, especially in processes that Public policies. It investigates this new context with the object of analysis being the public policy management councils and the national conferences.